PENGARUH KEPEMIMPINAN DIREKTIF, PENINGKATAN SUMBER DAYA MANUSIA DAN PERATURAN MENTERI PERHUBUNGAN NOMOR 78 TAHUN 2017 TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. BATAM TEKNIK DI LINE MAINTENANCE BANDAR UDARA INTERNASIONAL KUALANAMU - Robert Marganda Hutagalung; Inda Tri Pasa; Maria Marpaung; Putra Wiharja; Zulkifli . (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
This study aims to examine and analyze the effect of directive leadership, human resource improvement and The Minister of Transportation Regulation Number 78 Year 2017 on employee motivation at Kualanamu International Airport Line Maintenance of PT. Batam Teknik. Data collection was carried out by distributing questionnaires to 72 employees of Kualanamu International Airport Line Maintenance of PT. Batam Teknik. Data analysis in this study used SPSS version 22. The sampling technique used is the census method and data testing techniques used in this study include validity test, reliability test, classical assumption test and multiple linear regression analysis used to test and prove the research hypothesis. The results of the analysis show that directive leadership, increased human resources and The Minister of Transportation Regulation Number 78 Year 2017 have a positive and significant effect on employee work motivation simultaneously. This result can be seen from the calculated value of 31,587 with a significance value of 0.000 smaller than the significance limit of 0.050. The influence of directive leadership, increased human resources The Minister of Transportation Regulation Number 78 Year 2017 on employee motivation of 56.4% while the remaining 43.6% is explained by other factors outside of this study. Directive leadership, improvement of human resources and The Minister of Transportation Regulation Number 78 Year 2017 each partially affects employee motivation. This result can be seen from the calculated value of the directive leadership variable of 2.363with a significance value of 0.021 less than 0.050, and the calculated value of the human resource improvement variable of 2,089with a significance value of 0.040 less than 0.050 and the calculated value of the variable of The Minister of Transportation Regulation Number 78 Year 2017 is 2,012with a significance value of 0.048 less than 0.050.